Decolourization and Degradation of Dirct Azo Dyes and Biodegradation of Textile Dye Effluent by using Bacteria Isolated from Textile Dye Effluent - D. Stella, P. Saranraj*, V. Sumathi, D.Reetha and (Journal of Ecobiotechnology, 2010)
Abstract <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;"><span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Bacterial cultures isolated from the waste water treatment plant have the capacity to decoluorize and degrade the toxic Azo dyes. The present study was conducted to investigate the decolourization and degradation of Direct azo dyes and biodegradation of textile dye effluent by using bacteria isolated from textile dye effluent. Five different bacterial species were isolated from the textile dye effluent sample and the isolates were identified as Bacillus subtilis, Pseudomonas aeruginosa, Proteus mirabilis, Klebsiella pneumoniae and Escherichia coli. The bacterial inoculums were inoculated into flasks containing Direct azo dyes (500 mg/l) with trace amounts of yeast extract, glucose and sucrose and then sterilized and incubated for 4 days. The decolourization was expressed in terms of percentage decolourization. Pseudomonas aeruginosa (97.33%) was identified as the best decolourizer of Congo Red. Klebsiella pneumoniae (98.44%) was the best decolourizer of Viscose Orange â€“ A. The best decolourizer of Direct Green-PLS was Bacillus subtilis (99.05%). Klebsiella pneumoniae (87.27%) highly decolourized the Direct Violet-BL. Escherichia coli (61.56%) was the best decolourizer of Direct Sky Blue-FF. The best decolourizer of Direct Black-E was Klebsiella pneumoniae (92.03%). Bacterial biodegradation was assessed by physicohemical analysis.